Bilirubin Oxidase‐Based Nanobiocathode Working in Serum‐Mimic Buffer for Implantable Biofuel Cell. Issue 6 (22nd February 2013) - Gutiérrez‐Sánchez, Cristina; Pita, Marcos; Toscano, Miguel D.; De Lacey, Antonio L.
Abstract Low‐density graphite electrodes have been covalently modified with gold nanoparticles and used as scaffold for the oriented immobilization of Myrothecium verrucaria bilirubin oxidase. The developed nanobioelectrodes have been tested as a biocathode in a human‐serum surrogate buffer that mimics physiological conditions. The nanostructured bioelectrode offered a −140 µA cm−2 current density under serum‐mimic conditions at 0.2 V, and was operational during at least 6 days.